MODEL MINORITY: CUNNING ANTHROPOPHAGY OF TLAXCALTECAS IN NEW SPAIN - Montañez Pico, Daniel (2016)
The myth representing tlaxcaltecas as traitors obscures a fundamental aspect of its colonial history: It was one of the indigenous peoples who best knew how to learn and use in their favor social codes and legal and political logic of the Castilian conquerors. In a first explore how tlaxcaltecas participated in building its image as a “perfect vassals” of the Crown, secondly its strategic use of diplomatic embassies to Castile and, finally, issues related to their pictorial symbols. All subjects will be studied under the horizon of “cunning” (Simon Rodriguez) and “anthropophagy” (Oswald de Andrade) as forms of survival of our peoples.